The comparison of sprint reaction time and anaerobic power of young football players, volleyball players and wrestlers - Aksoy, Y.; Agaoglu, S. A. (Kinesiologia Slovenica, 2017)
This study was surveyed in order to compare and contrast the sprint, reaction time and anaerobic power of football players, volleyball players and wrestlers. The sportsmen were divided into 3 groups according to branches, andthe rates of speed, reaction time and anaerobic strength of sportsmen have been measured. Identification of the differences of the groups in terms of statistical evaluation for reaction time and minimum power in sport branches has been indicated by Kruskal Wallis and Dunn`s Multiple-Comparison test. On the other side, (one-way anova) and Tukey Multiple-Comparison test were used to indicate the differences among the branches in terms of sprint, peak power, average power and fatigue index. The measurements according to the branches are like below; reaction time 0.164 sec for footballers, 0.182 sec for volleyball players and 0.185 sec for wrestlers, Sprint time; 3.24 sec for footballers, 3.38 sec for volleyball players and 3.42 sec for wrestler; Peakpower; 278.51 watt for footballplayers, 263.23 for volleyball players and 235.51 for wrestlers; Average power; 209.51 watt for footballers, 207.05 watt for volleyball players and 180.97 watt for wrestlers; Minumum power; 166.55 watt for football players, 163.29 watt for volleyball players and 143.22 watt for wrestlers; Fatigue index; 2.48 watt/sec for football players, 2.23 watt/sec for volleyball players and 1.99 watt/sec for wrestlers. It is found out that there are considerable differences (P>0.05) in sprint, reaction time and anaerobic power values between football players and the other branches. As the trainings and matches of the football players mostly depend on leg-muscle strength and the leg-muscle strength is important for the measurements in the survey, footballplayers` anaerobic power and sprint values are beter than the other branches by considering the fact that reaction time is a part of speed.